Toward Holistic Assessment in Adult Islamic Religious Education: Integrating Irfani Epistemology and Andragogy - Willy Akmansyah Lubis; Fuji Pratami (AL-ISHLAH: Jurnal Pendidikan, 2026)
Conventional evaluation in adult Islamic Religious Education (PAI) remains predominantly rooted in pedagogical paradigms that prioritize cognitive achievement, thereby overlooking the spiritual and existential development central to adult learning.This conceptual study employs systematic library research, drawing on scholarly sources indexed in Scopus, Google Scholar, and DOAJ. Data were analyzed through qualitative content analysis to translate Irfani epistemological concepts into observable educational indicators.The study proposes a three-stage evaluation framework integrating spiritual-intuitive dimensions with andragogical principles: (1) Tazkiyah, assessing behavioral and affective alignment; (2) Kashf, evaluating reflective depth and existential awareness; and (3) Ta’bir, measuring value internalization through ethical decision-making narratives. The framework introduces non-grading instruments, including self-reflection journals and ethical dilemma portfolios, to shift assessment from rote learning toward indicators of spiritual maturity.This model offers a transformative approach to adult PAI evaluation by emphasizing personal growth, intrinsic motivation, and non-coercive learning environments over formal certification. It aligns assessment practices with the holistic nature of adult religiosity. However, as a conceptual framework, it lacks empirical validation. Future research should focus on instrument development, expert validation, and cross-cultural application to enhance its robustness and practical implementation.